ASSIMILATION OF THE MAIN ASSORTMENT OF ROD REINFORCING BAR OF DIE-ROLLED SECTIONS No 10-32 OF SOURCE CONTINUOUSLY-CASTED SLUGS OF SQUARE WITH SECTION 140X140 mm AT CONTINUOUS SMALL-SORT MILI 320 RUP “BMZ” . - M. A. Murikov; M. I. Titov; A. V. Rusalenko (Литьë и металлургия)
It is shown that in conditions of continuous small-section mill 320 RUP “BMZ” transfer to production of the main assortment of bar reinforcement of die-rolled sections No 10-32 of incoming billets of square with section 140x140 mm did not exert negative influence on the level of the reinforcing steel mechanical characteristics.